HABITUASI TRI SANDHYA SEBAGAI PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK DALAM MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SMP NEGERI 1 DENPASAR - Ni Putu Paramitha Rahayu Swastika; Heny Perbowosari; I Putu Agus Aryatnaya Giri (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the implementation of Tri Sandhya habituation, its supporting and inhibiting factors, and its implications for strengthening students’ religious character in Hindu Religious Education and Character Education at SMP Negeri 1 Denpasar. The study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the principal, Hindu Religious Education teachers, and students selected purposively. Data analysis followed the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings indicate that Tri Sandhya habituation has been routinely implemented and integrated into the school culture. Its implementation is supported by school commitment, teachers’ role modeling, a religious environment, and active student participation. The inhibiting factors include differences in students’ understanding of the meaning of Tri Sandhya, the influence of digital technology, and the tendency of some students to perform prayers merely as a routine activity. The habituation process positively contributes to strengthening religious character, as reflected in improved discipline, responsibility, self-control, religious awareness, and positive behavior among students. The study concludes that Tri Sandhya habituation is an effective strategy for fostering students’ religious character through consistent and continuous spiritual practices.